Pengaruh Pendapatan Asli Daerah, Dana Perimbangan dan Belanja Modal Terhadap Indeks Pembangunan Manusia Provinsi Jawa Timur Tahun 2014-2018 - Rezha Hanantoko (Economie: Jurnal Ilmu Ekonomi, 2020)
Welfare is the desire of human beings in life, by improving public welfare, this is the basis for the objectives in the State of Indonesia as stated in the opening of the 1945 Constitution because the fourth reason is that the community's welfare is expected by the regional government because it is able to reflect the achievements achieved by the region, from various efforts including activities. economy. This study aims to analyze the impact of local revenue, balance funds and capital expenditures on human development indicators in East Java Province. This type of research is a quantitative design. The object under study in this study is the province of East Java, while the population is the regency or city in the province of East Java. The sampling step uses non-probability sampling and the study steps used are panel data study methods. The results of the experiment with local revenue have a significant effect on the human development index, DBH has a significant effect on the human development index, DAU has a significant effect on the human development index, DAK has a significant impact on the human development index, Capital expenditure has a significant effect on the human development index.